2016
DOI: 10.1177/028072701603400302
|View full text |Cite
|
Sign up to set email alerts
|

School Construction as Catalysts for Community Change: Evidence from Safer School Construction Projects in Nepal

Abstract: Organizations in Nepal have retrofitted weak school buildings using earthquake-resistant construction techniques for over a decade. Some of these safer school projects have been carried out as technical interventions only, while others have been embedded within programs of community engagement, masonry training, and oversight. Following the 2015 Gorkha earthquake, 12 school sites were assessed through visual inspection and a series of community interviews to understand the impacts of safer school construction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…To build a culture of disaster prevention, various programs and international campaigns have been launched in different parts of the world, but in some of the most vulnerable and disaster-prone areas, there are still a large set of factors that must be addressed for this purpose. In addition to making various efforts to reduce loss of life, destruction of property, and disruption of society and economy, the objectives of disaster prevention programs also include building safer communities, particularly focusing on community participation in disaster prevention efforts, training programs for local masons and technicians, and disaster prevention-related training programs for students, teachers, and communities, e.g., [32][33][34][35][36][37].…”
Section: Awareness Building Program For Community Participation In Ma...mentioning
confidence: 99%
See 1 more Smart Citation
“…To build a culture of disaster prevention, various programs and international campaigns have been launched in different parts of the world, but in some of the most vulnerable and disaster-prone areas, there are still a large set of factors that must be addressed for this purpose. In addition to making various efforts to reduce loss of life, destruction of property, and disruption of society and economy, the objectives of disaster prevention programs also include building safer communities, particularly focusing on community participation in disaster prevention efforts, training programs for local masons and technicians, and disaster prevention-related training programs for students, teachers, and communities, e.g., [32][33][34][35][36][37].…”
Section: Awareness Building Program For Community Participation In Ma...mentioning
confidence: 99%
“…Without their involvement, the reconstruction program implementation may be sometimes misunderstood. Paci-Green et al [33] conducted a survey in this relation after the 2015 Nepal Earthquake. They reported that the community-engaged projects showed better knowledge of disaster risk and earthquake-resistant construction technology in people.…”
Section: Awareness Building Program For Community Participation In Ma...mentioning
confidence: 99%